TRENDS AND PATTERNS OF DRY SPELLS IN KARNATAKA - ARPITA PANDEY* and SRINIVASA SASDHAR PONNALURU, (The Journal of Research ANGRAU, 2021)
Drought affects agricultural growth by its duration and frequency. Karnataka an agrarian-basedeconomy, experienced frequent intense droughts in the last two decades. This study analyzed theintensity and duration of dry spells that occurred in Karnataka between 1990 and 2020 in the spatialcontext by using SPI. The Standardized Precipitation Index (SPI) helped in identifying four significantdrought incidents in the last three decades. Mann-Kendall Test was used to identify the trend in theSPI values. The results showed that the droughts in last decade were more intensive compared toprevious two decades. The duration of recent dry spells got overlapped between two different droughtperiods. The northern districts of State get more frequent dry spells compared to the southern districts.